Strategic Planning In School Case Study Of SMPN 1 Siak Hulu (Theoretical and Applied Studies) - Dinelti Fitria; Rhona Sandra; Rusdinal; Nurhizrah Gistituati (CV. AFDIFAL MAJU BERKAH, 2022)
Strategy implementation is the management process of realizing its strategy in the form of programs, procedures, budgets and strategy development in the form of actions. Principals are managers in schools who are expected to be able to implement strategies in schools so that educational goals in schools are still achieved and changes that occur can also be made. The principal must be able to seek a dynamic educational institution, so that the school he leads continues to live in the midst of such intense competition. The case study was conducted at SMP Negeri 1 Siak Hulu, Kampar Regency. From the results of the study it can be concluded that the implementation of the strategic plan at SMP Negeri 1 Siak Hulu went well under the leadership of the principal for the 2015-2022 period, namely Drs. Jasir, M.Pd, starting from setting the vision and mission, formulating the strategy, implementing the strategy, and evaluating & supervising the strategy.